In Ovo Injection of CHIR-99021 Promotes Feather Follicle Development via Modulating the Wnt Signaling Pathway and Transcriptome in Goose Embryos (Anser cygnoides) - Feng, Ziqiang; Gong, Haizhou; Fu, Jinhong; Xu, Xiaohui; Song, Yupu; Yan, Xiaomin; Mabrouk, Ichraf; Zhou, Yuxuan; Wang, Yudong; Fu, Xianou; Sui, Yujian; Liu, Tuoya; et al. (Frontiers in Physiology, 2022)
Feather plays important physiological functions in birds, and is also one of the economic productions in goose farming. Understanding and modulating feather follicles development during embryogenesis are essential for bird biology and the poultry industry. CHIR-99021 is a potent Wnt/ β-catenin signaling pathway activator that associated with feather follicles development. Here, goose embryos (Anser cygnoides) in ovo injection of CHIR-99021 was conduct at the beginning of feather follicles development (E9). The results showed that feather growth and feather follicles development were promoted. The Wnt signaling pathway was activated via inhibiting GSK-3β. Transcriptome analyses showed that the transcription changes were related to translation, metabolism, energy transport and stress in dorsal tissue of embryos received CHIR-99021, which might be to adapt and coordinate the promoted effects of CHIR-99021 on feather follicles development. This study suggests that in ovo injection of CHIR-99021 is a potential strategy to improve feather follicles development and feather-related traits for goose farming, and provides profiling of the Wnt signaling pathway and transcriptome in dorsal tissue of goose embryos for further understanding feather follicles development.